1989
DOI: 10.1128/jb.171.1.299-302.1989
|View full text |Cite
|
Sign up to set email alerts
|

Lysine catabolism in Streptomyces spp. is primarily through cadaverine: beta-lactam producers also make alpha-aminoadipate

Abstract: Genetic and biochemical evidence was obtained for lysine catabolism via cadaverine and 8-aminovalerate in both the P-lactam producer Streptomyces clavuligerus and the nonproducer Streptomyces lividans. This pathway is used when lysine is supplied as the sole source of diitrogen for the organism. A second pathway for lysine catabolism is present in S. clavuligerus but not in S. lividans. It leads to oa-aminoadipate, a precursor for ,-lactam biosynthesis. Since it does not allow S. clavuligerus to grow on lysine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 17 publications
1
39
0
1
Order By: Relevance
“…Previously, we showed that lysine r-aminotransferase (LAT) activity and a-aminoadipate synthesis occur only in 3-lactam-producing actinomycetes (12). Here we report that LAT is governed by DNA located within the cluster of ,B-lactam biosynthesis genes in S. clavuligerus.…”
Section: Streptomyces Clavuligerus Is a Gram-positive Mycelialmentioning
confidence: 84%
See 1 more Smart Citation
“…Previously, we showed that lysine r-aminotransferase (LAT) activity and a-aminoadipate synthesis occur only in 3-lactam-producing actinomycetes (12). Here we report that LAT is governed by DNA located within the cluster of ,B-lactam biosynthesis genes in S. clavuligerus.…”
Section: Streptomyces Clavuligerus Is a Gram-positive Mycelialmentioning
confidence: 84%
“…Labeling with [32P]dCTP was by random primer extension, using a kit from Boehringer Mannheim, Dorval, Quebec. LAT activities were assayed as described previously (12).…”
Section: Methodsmentioning
confidence: 99%
“…In actinomycetes, LAT is found only in the P-lactamproducing species and is not needed for sustaining growth on L-lysine (21). The gram-negative bacterium Flavobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Madduri et al (21) reported that in these actinomycetes, L-lysine-e-aminotransferase (LAT) is specific to P-lactam (cephamycin C) producers and provides the precursor for antibiotic synthesis; the pathway via cadaverine is obligatory for lysine catabolism (Fig. 1).…”
mentioning
confidence: 99%
“…In streptomycetes, where aspartate is a precursor not only of the related protein amino acids but sometimes also of secondary metabolites, there is evidence that regulatory mechanisms acting on core reactions in the aspartate pathway control the flow of metabolic intermediates to such products as the p-lactam antibiotics, which are derived from lysine via L-a-aminoadipic acid (Whitney e t al., 1972;Madduri et al, 1989; Vining e t a/., 1990). I3oth Ask and Asd have been partially purified from StreptornJyces clavuligerus (Mendelovitz & Aharonowitz, 1982 Sambrook et al (1989).…”
Section: Introductionmentioning
confidence: 99%